Implementasi Algoritma Genetika pada Penjadwalan Job Shop - Fithri Selva Jumeilah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2015)
In the industry to create a product is divided into several processes and each process requires a different machine to process during a certain time unit. If not scheduled properly, it will take a long time to produce. Scheduling is the process of determining a resource that will process the job with a certain order for a certain time. The more jobs and machines, the more difficult transfers. Good scheduling is who has the time or the completion of all work is often referred to (makespan) and the smallest waiting time machine. To obtain the best schedule quickly it takes a scheduling application that implements a genetic algorithm. This study uses metododologi software development Rational Unified Process. From the results of this study showed that the schedule generated by the genetic algorithm approach is best scheduling. This is evidenced by the results of tests resulted in the percentage accuracy of 94.3%.